Utilizing legacy seismics and non-seismic geophysical methods for deep mineral targeting and near-surface characterization: implications for mine development planning - Mutshafa, Ndamulelo (University of the Witwatersrand, Johannesburg, 2023)
This thesis demonstrates through several case studies how the reprocessing of legacy reflection seismic data using advanced algorithms can be of value to mineral exploration and mine development, especially in hard-rock environments. The thesis also showcases how the integration of seismic and non-seismic geophysical datasets can assist in delineating near- surface geological structures (e.g., boulders and fractures) for mine planning and designs. Papers I and II demonstrate how the reprocessed legacy reflection seismic data have been used to delineate and image the world-class gold deposits such as the Black Reef (BLR) and Ventersdorp Contact Reef (VCR) of the Witwatersrand goldfields in South Africa. The two legacy reflection seismic profiles (Paper I) were acquired in 1988 for deep mineral exploration and mine planning over an area that is dominated by dolomitic outcrops that cause scattering of seismic energy at the near-surface, preventing energy propagation into the subsurface. Various migration approaches, namely, pre-stack time, pre-stack depth, and post-stack time migration were applied to test their capabilities in improving structural imaging. Reprocessing results from the pre-stack depth migration using the Kirchhoff algorithm provided the most improved subsurface images, especially the deeper targets due to its ability to honour complex lateral variations in the velocity field. In addition, Kirchhoff's pre-stack and post-stack time migration techniques improved the continuity of the near-surface reflections below the dolomitic rocks. Paper II presents the results from the recovered and processed 25.3 km long legacy seismic survey that was acquired in 1983 by the Gold Division of Anglo-American as part of the Witwatersrand goldfields exploration program. The reprocessing of the data improved the imaging of the gold-bearing horizon termed Ventersdorp Contact Reef (VCR), which is situated at depths between ~2400 and ~4100 m below the ground surface near the South Deep mine in Fochville, South Africa. The pre-stack time and phase-shift migration approaches were tested during processing, and both revealed a dipping reflection associated with the gold-bearing horizon and major steeply dipping faults that crosscut and displace the deposit. The interpretation of the results was constrained using borehole logs and surface geology. This is encouraging and motivates the use of legacy seismic data in the exploration of deep-seated targets. Papers III, IV and V present the results from the use of multi-geophysical methods (resistivity, magnetics, seismic, ground penetrating radar and multichannel analysis of surface waves) at Tharisa platinum mine to provide a comprehensive understanding of the subsurface geology by accurately delineating and locating boulders, mapping fractures and groundwater aquifers to improve Platinum Group Elements (PGEs) mining efficiency and reduce risks. The results from these integrated geophysical methods were successful in complementing each other in terms of providing a clear picture of the near-surface geological structures to help the mine plan better for future operations.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy In the Faculty of Science, School of Geosciences University of the Witwatersrand, Johannesburg 2023
Keywords: Siesmics; Data processing; Exploration; UCTD; SDG-15: Life on land